miR-3940-5p reduces amyloid β production via selectively targeting PSEN1 - Qi, Yanmei; Wang, Xu; Guo, Xihan (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by the accumulation of amyloid beta (Aβ) in brain. Mounting evidence has revealed critical roles of microRNAs (miRNAs) in AD pathogenesis; however, the miRNAs directly targeting presenilin1 (PSEN1), which encodes the catalytic core subunit of γ-secretase that limits the production of Aβ from amyloid precursor protein (APP), are extremely understudied. The present study aimed to identify miRNAs targeting PSEN1 and its effect on Aβ production. In-silico analysis suggested miR-3940-5p as a candidate miRNA, which was experimentally validated via luciferase reporter assays. miR-3940-5p overexpression significantly reduced PSEN1 mRNA and protein in SH-SY5Y cells. Conversely, inhibition of miR-3940-5p resulted in increased PSEN1 mRNA levels. Transient transfection of miR-3940-5p mimics to SH-SY5Y-APP swe cells led to a significant reduction in the production of Aβ42 and Aβ40. Lentiviral-mediated miR-3940-5p overexpression significantly decrease the expression of PSEN1 and did not significantly impact the expression of other predicted target genes. In SH-SY5Y-APP swe stably overexpressing miR-3940-5p mediated by lentivirus, the expression of PSEN1 and the production of Aβ42 and Aβ40 were also significantly decreased. Hence, for the first time, our findings demonstrate the functional importance of miR-3940-5p in antagonizing Aβ generation via specifically and directly targeting PSEN1.